2022
DOI: 10.1186/s12935-022-02631-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of anti-cancer effects of novel protein disulphide isomerase (PDI) inhibitors in breast cancer cells characterized by high and low PDIA17 expression

Abstract: Background Protein disulphide isomerases (PDIs) play an important role in cancer progression. However, the relative contribution of the various isoforms of PDI in tumorigenesis is not clear. Methods The content of PDI isoforms in 22 cancer cells lines was investigated using LC–MS/MS-based proteomic analysis. The effects of PDIA1, PDIA3 and PDIA17 inhibition on the proliferation, migration and adhesion of MCF-7 and MDA-MB-231 cells, identified as hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…In the present work, we focused on PDI, the prototype of the PDI family, as the target of JUG derivatives. In addition to PDI, ERp57 (PDIA3) and ERp72 (PDIA4) are two other major members of the PDI family in both platelets and A549 cells. , Therefore, the selectivity of compounds 18 and 22 against PDI over ERp57 and ERp72 were examined. As shown in Table , 18 and 22 inhibited ERp57 and ERp72 at concentrations about 4 to 7-fold higher than that required to inhibit PDI.…”
Section: Resultsmentioning
confidence: 99%
“…In the present work, we focused on PDI, the prototype of the PDI family, as the target of JUG derivatives. In addition to PDI, ERp57 (PDIA3) and ERp72 (PDIA4) are two other major members of the PDI family in both platelets and A549 cells. , Therefore, the selectivity of compounds 18 and 22 against PDI over ERp57 and ERp72 were examined. As shown in Table , 18 and 22 inhibited ERp57 and ERp72 at concentrations about 4 to 7-fold higher than that required to inhibit PDI.…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have reported inhibition of cell proliferation and/or cell cycle progression in breast cancer cell lines upon pharmacological PDI-inhibition or PDIA3 silencing ( 121 , 122 , 128 , 133 ). In one study, PACMA-31 had stronger effects than 16F16 in inhibiting proliferation of MCF-7 or MDA-MB-231 cells ( 115 ).…”
Section: Pdis In Cancer: Relevance To the Tumor Microenvironmentmentioning
confidence: 99%
“…AGR2 was found by comparing the protein differences between ER positive and negative breast cancer cells ( 1 ). AGR2 only expressed in ER positive breast cancer cell lines, such as MCF7, T-47D, BT-474 and ZR-75, but not in ER negative breast cancer cell line MDA-MB-231 ( 66 ), which attracted a lot of attention once it was found, as described in Table 2 . Later, experiments in vivo ( 75 ) and in vitro ( 5 ) confirmed that the expression of AGR2 protein was indeed regulated by estrogen.…”
Section: The Clinical Association Between Agr2 and Breast Cancermentioning
confidence: 99%